Abstract explorations in acrylic painting fun, creative & innovative techniques - Toye, Jo (North Light Books, 2016)
"Like a diving board for creativity, Abstract Explorations in Acrylic Painting will help you plunge joyfully into artmaking. With the belief that an attitude of playfulness is key to artistic growth, award-winning acrylic artist Jo Toye leads you on an engaging workshop-style adventure filled with innovative techniques, inventive approaches and breakthrough results."--Provided by Amazon.com.